KNOWLEDGE AND PRACTICES REGARDING SALT CONSUMPTION AND ASSOCIATED FACTORS AMONG STUDENTS AT VINH MEDICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe students’ knowledge and practices regarding salt use and to identify related factors.Methods: A cross-sectional descriptive study was conducted among 435 students enrolled in medical and bachelor programs at Vinh University of Medicine.Results: Only 39,1% of students correctly knew the salt intake recommended by the World Health Organization. A total of 57,2% of students frequently/always added salt or salty seasonings during food marination or preparation, and 73,3% frequently/always added salt or salty seasonings during cooking. The most commonly practiced salt-reduction behavior was diluting dipping sauces during meals (51,2%). There were statistically significant associations between gender, religion, meal patterns, and personal food preferences with the mean knowledge and practice scores regarding salt use among students.Conclusion: Students’ knowledge and practices regarding salt use remain inadequate. It is necessary to strengthen health communication and education activities and to integrate salt-reduction content into training curricula in order to improve students’ salt-use behaviors.
Keywords: Students, salt, salt use.